Building bridges for dance through arts-based research. Issue 2 (4th May 2017) - Wilson, Lisa; Moffett, Ann-Thomas
Abstract: This paper considers arts-based research (ABR) as a useful resource for creating fluid and dialogic spaces between multiple domains of dance knowledge and practices. Through the lens of a multi-disciplinary, arts-based research project Same Story, Different Countries explored the socio-political phenomena of racism in the United States and South Africa. The paper illuminates how arts-based research can bridge important areas of learning, in particular artistic knowledge and social justice learning for postsecondary dance students, teachers and artists. Using a mixed method of qualitative techniques and artistic dance practices the study captured and analyzed dance participants' perspectives on the benefits of being involved in the project. The project was found to increase participants' knowledge of various dance practices (performance, choreography, teaching, research) while simultaneously deepening their understanding of racism and racial injustice, and awakening their sense of social responsibility. Three major themes emerged from the findings: connectedness, transformation and empowerment toward action in future dance practices. In empowering the dance participants, and creating bridges for them between dance and its multiple domains, and dance and the larger social world, this paper advocates that arts-based research is valuable to the future growth and relevance of postsecondary dance education.